Collaborative Leadership Practices in Early Childhood Education: A Systematic Review of School Planning and Management Approache - Azizah, Nur; Riswandi, Riswandi; Hariri, Hasan (Journal of Educational Management Research, 2025)
This study explores the role of collaborative leadership in enhancing the effectiveness of education delivery through school planning and management. Using a systematic literature review with a narrative approach, eight peer-reviewed articles from Google Scholar and SINTA were analyzed. Findings reveal that collaborative leadership fosters participatory, transparent, and student-centered planning processes. Principals, as collaborative leaders, actively engage teachers, staff, and stakeholders in joint decision-making, which strengthens ownership, shared responsibility, and the overall quality of educational services. Key challenges identified include ineffective communication, resistance to change, and limited managerial competence. The study underscores that open, inclusive, and reflective leadership enables schools to adapt planning strategies to evolving challenges and community needs. From a management perspective, the findings highlight that collaborative leadership not only improves operational efficiency but also builds organizational resilience, strengthens stakeholder trust, and promotes sustainable institutional growth. These insights have broader implications for educational management, suggesting that leadership development programs should integrate collaborative competencies as a core component. By embedding collaboration into school planning, educational institutions can create dynamic, responsive, and high-performing learning environments.